Chemical shipments through the Straits of Malacca: An analysis from a Malaysian legal perspective/ Wan Siti Adibah binti Wan Dahalan - Wan Siti Adibah, Wan Dahalan (2011)
For an effective maritime safety culture, many States believed in the establishment of the International Maritime Organisation (IMO), 1 a permanent body that would be able to coordinate the international nature of the shipping industry. This chapter examines principally the IMO's international conventions on safe and secure navigation, marine pollution control, liability and compensation and other waste control provisions and regional/sub-regional chemical spill contingency response action plans that impact upon HNS shipments in the Straits of Malacca (the Straits) as they form the underlying bases of protection of the Straits from HNS pollution. The examination starts with a discussion of international environmental law principles on marine pollution control that are needed to support the transit passage regime in the Straits. In particular, this chapter highlights the importance of ratification of the 1996 HNS Convention and the 2010 HNS Convention Protocol and the 2000 OPRC-HNS Protocol by Malaysia for implementation in the Straits. 3.2 ENVIRONMENTAL LAW PRINCIPLES 3.2.1 Sustainable Development 1 IMO is the United Nations specialized agency responsible for improving maritime safety and preventing pollution from ships.20Decem.2008,12.30pm< http://www.imo.org.>. The IMO as it was renamed in 1982 (formerly called the Inter-Governmental Maritime Consultative Organisation -IMCO) is one of the oldest United Nation Organisations and the IMO Convention was opened for signature at Geneva on 6 March 1948. One of the purposes of the organisation is to “provide machinery for cooperation among Governments in the field of governmental regulation and practices relating to technical matters of all kinds affecting shipping engaged in international trade; to encourage and facilitate the general adoption of the highest practicable standards in matters concerning maritime safety, efficiency of navigation and prevention and control of marine pollution from ships, Article 1 (a) IMO Convention. Basic Documents, Volume One, 2004 edition.